2023
DOI: 10.24198/responsive.v5i4.44555
|View full text |Cite
|
Sign up to set email alerts
|

Persepsi Masyarakat Terhadap Tren Perkembangan Industri Halal Di Media Sosial: Analisis Respons Di Indonesia

Abstract: Penelitian ini bertujuan untuk menganalisis sentimen masyarakat yang diwakili oleh pengguna Twitter terkait industri halal setelah pandemi COVID-19. Metoda yang digunakan adalah Analisis Jaringan Sosial (SNA) dengan menggunakan Drone Emprit. Data diambil dari arsip atau dokumen tertulis, gambar, atau rekaman video yang diproduksi, didistribusikan, dan diterima oleh pengguna media sosial Twitter pada periode Maret 2022 hingga Agustus 2022. Hasil penelitian menunjukkan bahwa narasi yang berkembang di masyarakat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(11 reference statements)
0
0
0
Order By: Relevance
“…As for this collection using keyword restrictions, namely "bank", "banking", and "sharia". Furthermore, the Twitter developer provides the Twitter Search API to get near-real-time access to the latest collection of tweets published in the last 7 days filtered through a specific query (Miftahuddin et al, 2023). The results displayed were in the form of percentage trends, retweet relationships, mention trends graphs, most retweeted statuses, conversation trends.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As for this collection using keyword restrictions, namely "bank", "banking", and "sharia". Furthermore, the Twitter developer provides the Twitter Search API to get near-real-time access to the latest collection of tweets published in the last 7 days filtered through a specific query (Miftahuddin et al, 2023). The results displayed were in the form of percentage trends, retweet relationships, mention trends graphs, most retweeted statuses, conversation trends.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, these data can make a reference for reading various and current social phenomena (Arianto, 2020). The "lexicon" method is utilized to classify public conversations based on sentiment by collecting words classified as positive, negative, or neutral (Miftahuddin, 2023). As for the research process shown in Figure 1, the API performed a DEA search (Step 1) to collect the requested tweets and the data was collected from Twitter Streaming and Twitter Crawl (Step 2) and processed them into the index server based on the SOLR system described in the DEA big data architecture framework as shown in figure 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation